A comparative UHPLC-QqQ-MS-based metabolomics approach for evaluating Chinese and North American wild rice. (1st March 2019) - Yan, Ning; Du, Yongmei; Liu, Xinmin; Chu, Meijun; Shi, John; Zhang, Hongbo; Liu, Yanhua; Zhang, Zhongfeng
Highlights: Chinese and North American wild rice differ in secondary metabolite composition. Differential secondary metabolites were compared using UHPLC-QqQ-MS. Zizania latifolia and Z. palustris had 357 differential metabolites. "Phenylpropanoid biosynthesis" pathway showed significant enrichment. We provide solid reference values for functional food development from wild rice. Abstract: Wild rice ( Zizania spp.) is considered by many consumers to be a health-promoting food. The perennial Z. latifolia (native to Asia) and annual Z. palustris (native to North America) are crops to produce Chinese and North American wild rice, respectively. In this study, we compare the metabolomes of the two species using a UHPLC-QqQ-MS-based metabolomics approach. In total, 672 metabolites were identified; of those, 357 showed differential expression (160 up-regulated versus 197 down-regulated). Metabolic pathway analysis of these differential metabolites showed a significant enrichment of the "Phenylpropanoid biosynthesis" pathway. A hierarchical cluster analysis of differential metabolites of the two species showed a clear grouping pattern in which the relative contents of five anthocyanins and four catechin derivatives differed significantly between the two groups. This study provides reference values for isolation and identification of functional compounds from wild rice and for research and development of functional foods from the two species.